The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s1010-7940(99)00346-2
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term results after the modified Cox/Maze procedure combined with other cardiac surgery

Abstract: The medium-term results after the modified Cox/Maze III procedure concomitant with other cardiac procedure are good with improved functional status and good survival rate. However, there seems to be gradual but constant attrition in the rate of SR maintenance in SR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…With the implementation of the maze III procedure and with the use of alternative sources of energy, the frequency of pacemaker placement has decreased to 5-13% according to several studies 18,22,27,30,39 . Other authors assessed the need for permanent cardiostimulation after surgery as, as much as 20% (ref.…”
Section: Discussionmentioning
confidence: 99%
“…With the implementation of the maze III procedure and with the use of alternative sources of energy, the frequency of pacemaker placement has decreased to 5-13% according to several studies 18,22,27,30,39 . Other authors assessed the need for permanent cardiostimulation after surgery as, as much as 20% (ref.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, many other long-term results of the maze procedure showed a gradual attrition rate of freedom from AF during the follow-up period [13,18,20]. This study also showed a progressively decreased maze success rate at 3, 5, 7, and 9 years after operation; 86.5%, 82.2%, 75.4%, and 69.8% respectively.…”
Section: Discussionmentioning
confidence: 47%
“…Conversely, actuarial methods used to delineate time-related events, 'AF recurrence-free rate' define any recurrent AF as a failure of the procedure, which may underestimate the actual clinical success rate. Since the most favorable method of the reporting the success rate is 'rhythm at last follow-up' [17][18][19], the method was adopted to evaluate the success and failure of maze procedures in this study. Looking at the definition of maze success, the reported clinical results of maze procedures were variously expressed, such as 'freedom from AF recurrence', and 'normal sinus rhythm restoration rate'.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial flutter can effectively be abolished using conventional techniques, and can be oriented on electro-anatomic maps. We previously reported that the Maze procedure is useful for patients with chronic AFIB [16][17][18][19]. Recently, both human and animal studies have demonstrated that the PV and the posterior left atrial wall are important in triggering and driving fibrillation activity [1].…”
Section: Clinical Applicationsmentioning
confidence: 99%